The Umbrella Academy. Volume 3, Hotel Oblivion - Way, Gerard (Dark Horse Books, 2019)
"Faced with an increasing number of lunatics with superpowers eager to fight his own wunderkind brood, Sir Reginald Hargreeves developed the ultimate solution... But their past is coming back to haunt them."--Provided by publisher.